Making or breaking - Key success factors in the air cargo market. (June 2017) - Merkert, Rico; Van de Voorde, Eddy; de Wit, Jaap
Abstract: This introductory paper considers a number of major evolutions in the air freight market. In the first instance, it describes the heterogeneous environment in which air cargo services are performed. Subsequently, it looks at some of the most notable developments in air freight. Lastly, it deals with the market structure and with possible future strategies.